The Lamb's Head as a Model for Surgical Skills Development in Endonasal Surgery - Mallmann, Luíza Baptista; Piltcher, Otávio Bejzman; Isolan, Gustavo Rassier (Journal of Neurological Surgery Part B: Skull Base, 2016)
Objectives To test the viability of a lamb's head model for sinonasal surgery training in Brazil by comparing performance of endoscopic procedures in the septum and inferior turbinates.Design Prospective study.Settings Universidade Federal do Rio Grande do Sul (2015).Participants Ten physicians performed septoplasty, inferior turbinoplasty, and middle turbinectomy on 30 lamb's heads.Main Outcome Measures Degree of difficulty and similarity, opinion of tissue color and texture, and degree of satisfaction.Results Participants completed a questionnaire at the end of each procedure and a satisfaction survey at the end of the project. Significant between-group differences were found for the perceived degree of difficulty in performing left inferior turbinoplasty, right inferior turbinoplasty, and septoplasty. Final satisfaction with training was scored 9 out of 10, and all participants reported that they would like to receive such training again.Conclusion The tested model is feasible due to its low cost, its easy availability, and its similarity to human anatomy in terms of dimensions of relevant structures and tissue consistency. It allows effective training in instrument handling and acquisition of the surgical skills related to two-dimensional vision needed for endoscopy. However, it should not be considered a substitute for training of specific surgical techniques.
Keywords: paranasal sinus; animal model; training technique; surgery; education